Supporting Clean Energy in the ASEAN: Policy Opportunities from Sustainable Aviation Fuels Initiatives in Indonesia and Malaysia - Atmowidjojo, A. (IOP Publishing Ltd, 2021)
Sustainable aviation fuels is a strategic long-term solution for zero-carbon aviation industry by 2050, thus underscoring the need to accelerate the deployment through reforms in the relevant key areas. Aligned to the agenda, this paper aims to study the policy opportunities for drop-in sustainable aviation fuel (SAF) deployment in the ASEAN by considering the initiatives undertaken. by Indonesia and Malaysia. Four areas are used as coding framework to assess the current status, challenges, and policy opportunities, namely (1) policy, strategy, and reforms; (2) standards and certification system; (3) economic instruments; and (4) international integration. First, the current status and challenges within each country is assessed. Indonesia has shown a more command-and-control approach with an upfront SAF blending mandate. However, it needs to be supported by several compliance measures. Malaysia, on the other hand, has conducted country assessments but no SAF-specific policy has been issued yet. Both countries still lack the economic instruments, while international integration is still relatively under-explored with only limited inter-regional partnerships. As the biggest palm-oil producing countries, Indonesia and Malaysia possess enormous potentials to lead the region in deploying SAF, thus more initiatives are urged. Â© Published under licence by IOP Publishing Ltd.